Robust Selections of Various Hematopoietic Cell Fractions on the CliniMACS Plus Instrument - Sandhya R. Panch; Opal L. Reddy; Katherine Li; Thejaswi Bikkani; Anusha Rao; Swathi Yarlagadda; Steven Highfill; Daniel Fowler; Richard W. Childs; Minocher Battiwalla; John Barrett; Andre Larochelle; et al. (Clinical Hematology International, 2019)
Cell separation technologies play a vital role in the graft engineering of hematopoietic cellular fractions, particularly with the rapid expansion of the field of cellular therapeutics. The CliniMACS Plus Instrument (Miltenyi Biotec) utilizes immunomagnetic techniques to isolate hematopoietic progenitor cells (HPCs), T cells, NK cells, and monocytes. These products are ultimately used for HPC transplantation and for the manufacture of adoptive immunotherapies. We evaluated the viable cell recovery and cell purity of selections and depletions performed on the CliniMACS Plus over a 10-year period at our facility, specifically assessing for the isolation of CD34+, CD4+, CD3+/CD56+, CD4+/CD8+, and CD25+ cells. Additionally, patient- and instrument-related factors affecting these parameters were examined. Viable cell recovery ranged from 32.3 ± 10.2% to 65.4 ± 15.4%, and was the highest for CD34+ selections. Cell purity ranged from 86.3 ± 7.2% to 99.0 ± 1.1%, and was the highest for CD4+ selections. Undesired cell fractions demonstrated a range of 1.2 ± 0.45 to 5.1 ± 0.4 log reductions. Red cell depletions averaged 2.12 ± 0.68 logs, while platelets were reduced by an average of 4.01 ± 1.57 logs. Donor characteristics did not impact viable cell recovery or cell purity for CD34+ or CD4+ cell enrichments; however, these were affected by manufacturing variables, including tubing size, bead quantity, and whether preselection platelet washes were performed. Our data demonstrate the efficient recovery of hematopoietic cellular fractions on the CliniMACS Plus that may be optimized by adjusting manufacturing variables.